PENERAPAN PERSAMAAN UNSUR POKOK DALAM SENGKETA MEREK TERKENAL BERDASARKAN UNDANG-UNDANG NOMOR 15 TAHUN 2001 TENTANG MEREK (Analisis Putusan Mahkamah Agung Nomor : 022.K/N/HAKI/2002) - KARTAWIDJAYA, JUANDA (Dinamika Hukum, 2017)
Cornetto as well-known foreign brands are having legal problems withtheir registration Campina Cornetto with No. Registration 425 985 in the Office ofthe Director of IPR. Registration Campina Cornetto have similarities in principlewith Cornetto that are well known. Therefore, pursuant to Article 76 of Undang-Undang No. 15 of 2001 on the marks, the Cornetto filed for cancellation oftrademark registration in the commercial court, the case is decided in the Supremeappeal through the Putusan Mahkamah Agung No. 022.K / N / HAKI / 2002.This research aims to determine the application of similarity in principlein dispute famous brand between Cornetto against Campina Cornetto, and basicconsideration both the judges and the judges judex factie and judex juris inimplementing elements of similarity in principle in the case of the mark.This research method is a normative juridical research, which refers tothe legal norms contained in the legislation, international conventions, and thecourt ruling. This study seeks to cultivate primary and secondary legal materialthat has been collected is then given ratings (evaluation) using deductive logic,namely by pulling off a major premise to the minor premise, then performedfurther interpretation and arguments filed. Furthermore, the authors provide anassessment of right or wrong or what should be according to the law or legalevents of the research results.The results of this research is to show that the registration of CampinaCornetto there are similarities in principle to Cornetto, as foreign brands are wellknownin advance. The panel of judges in applying the similarity in principle canbe seen from the form, placement means, ways of writing, and pronounciation, aswell as combinations of these elements. In addition, the similarity in principle intrademark disputes have accompanied any element of bad faith of the defendant /respondent appeal. The cornerstone of the application of the equation principallymeasured based on legal regulations of national and international as well as seethe knowledge society to the development of the mark in question.Keywords: Law of Trademarks, Equation In any case, and well-known mark